Impact of Electronic Billing Machine (EBM) on Vat Compliance Among Small and Medium Sized -Enterprises in Rwanda (Global Journal of Management and Business Research, 2019)
This study aimed at assessing the impact of Electronic billing machine on VAT compliance on Small and Medium -Size Enterprises in Rwanda. The main challenge in the administration of Value Added Tax (VAT) in many countries, has mainly been tax evasion by non-issuance of tax invoices especially by small to medium taxpayers. Electronic Billing Machines (EBMs) enable revenue authorities to monitor formal business transactions and thus offer the potential to improve VAT compliance, however, because firms can choose not to issue receipts or issue false receipts, EBMs have limited benefits to VAT collections. Descriptive method was used to collect data, data gathered was analyzed, interpreted and presented. A sample size of 159 people grouped into Medium taxpayers, Small taxpayers and staff of RRA Musanzestation was randomly selected from a population of 709 VAT registered taxpayers located in Tax centre of Musanze. Primary and secondary data was used in this research.
Keywords: electronic billing machine (EBM); vat compliance; small and medium size enterprises